2019
DOI: 10.1002/kin.21314
|View full text |Cite
|
Sign up to set email alerts
|

Shock tube investigation of methyl tert butyl ether and methyl tetrahydrofuran high‐temperature kinetics

Abstract: The autoignition and pyrolysis of two C5 ethers, methyl tert butyl ether (MTBE) and 2‐methyltetrahydrofuran (2‐MTHF), are investigated using the shock tube reactor. The experiments are carried out at pressures of 3.5 and 12 atm at temperatures above 1000 K with argon as a diluent gas. By means of direct laser absorption, carbon monoxide time histories and associated chemical kinetic timescales are also determined. It is observed that the competition between ignition and pyrolysis times depends on the temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…High-temperature IDTs of 2-MTHF were measured in STs by Wang et al [661,662] and Jouzdani et al [664,665]. Tripathi et al [663,669], Fenard et al [670], and Cai et al [672] reported IDTs obtained in STs for 2-MTHF, 2,5-DMTHF, and 2-BTHF, respectively.…”
Section: Thf Substituted By Alkyl Chainsmentioning
confidence: 99%
See 1 more Smart Citation
“…High-temperature IDTs of 2-MTHF were measured in STs by Wang et al [661,662] and Jouzdani et al [664,665]. Tripathi et al [663,669], Fenard et al [670], and Cai et al [672] reported IDTs obtained in STs for 2-MTHF, 2,5-DMTHF, and 2-BTHF, respectively.…”
Section: Thf Substituted By Alkyl Chainsmentioning
confidence: 99%
“…An explanation for this trend is given in Part 5.2.2.4. High-temperature (> 900 K) products, as summarized in Table 16, were measured for 2-MTHF (FR and ST pyrolysis [658,664] and PLF [658,667,668]) and for 2,5-DMTHF (FR pyrolysis [671]). No speciation data was found for any other molecules of this class.…”
Section: Thf Substituted By Alkyl Chainsmentioning
confidence: 99%
“…The combustion chemistry of MTHF has been investigated extensively, ,,,,, and various kinetic models have been reported, such as those by De Bruycker et al, Moshammer et al and Fenard et al, whereas the current knowledge of the oxidation chemistry of THFA is limited to the recent investigation by Tran et al The authors explored the THFA combustion chemistry of a low-pressure-burner-stabilized 20% THFA/methane flame. Only one fuel mixture (20% THFA) was investigated, and numerous intermediate and final products were identified and quantified.…”
Section: Introductionmentioning
confidence: 99%